A view on Europeana from the US perspective - Erway, Ricky (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
At the express request of the organisers of the second LIBER/EBLIDA workshop on digitization, Ricky Erway of OCLC provided an outsider’s view on the Europeana project. Erway looks at Europeana from many vantage points: mandate and funding; branding and public relations; learning from others; aggregation; cooperation; content; rights; metadata; technology; access; user feedback; and sustainability – offering valuable advice for the Europeana community in doing so.